Analisis Profitabilitas, Likuiditas, Struktur Modal dan Ukuran Perusahaan terhadap Nilai Perusahaan - Jeany Berty Tylova; M Hendri Yan Nyale (LPPM Institut Nasional Laa Roiba Bogor, 2023)
The purpose of this study is to investigate the effects of company size, profitability, liquidity, capital structure, and firm value. The population in this study is listed on the Indonesia Stock Exchange between 2018 and 2021 and consumes beverages in the food subsector. Using a purposive sampling strategy, this research model generated 48 sample data from 12 companies chosen as samples. ROA is used as a proxy for profitability by dividing net income by total assets. The proxy for liquidity is the current ratio, which is the ratio of current assets to current liabilities. The DER proxy, which is the formula for total debt divided by total equity and company size using natural logarithms (total assets), and the PBV, which is the market price per share divided by book value per share, are utilized in the capital structure. Using SPSS (Statistics Product and Service Solution) and assistive technology, multiple linear regression analysis models are utilized for hypothesis testing. Firm value is positively impacted by profitability, liquidity, and firm size, according to the findings of this study, whereas firm value is negatively impacted by capital structure. Keywords: Firm Value, Profitability, Liquidity, Capital Structure, and Company Size